Recently Evolved Francisella-Like Endosymbiont Outcompetes an Ancient and Evolutionarily Associated Coxiella-Like Endosymbiont in the Lone Star Tick (Amblyomma americanum) Linked to the Alpha-Gal Syndrome - Kumar, Deepak; Sharma, Surendra Raj; Adegoke, Abdulsalam; Kennedy, Ashley; Tuten, Holly C.; Li, Andrew Y.; Karim, Shahid (Frontiers in Cellular and Infection Microbiology, 2022)
Background Ticks are hematophagous arthropods that transmit various bacterial, viral, and protozoan pathogens of public health significance. The lone star tick (Amblyomma americanum) is an aggressive human-biting tick that transmits bacterial and viral pathogens, and its bites are suspected of eliciting the alpha-gal syndrome, a newly emerged delayed hypersensitivity following consumption of red meat in the United States. While ongoing studies have attempted to investigate the contribution of different tick-inherent factors to the induction of alpha-gal syndrome, an otherwise understudied aspect is the contribution of the tick microbiome and specifically obligate endosymbionts to the establishment of the alpha-gal syndrome in humans. Materials and Methods Here we utilized a high-throughput metagenomic sequencing approach to cataloging the entire microbial communities residing within different developmental stages and tissues of unfed and blood-fed ticks from laboratory-maintained ticks and three new geographical locations in the United States. The Quantitative Insights Into Microbial Ecology (QIIME2) pipeline was used to perform data analysis and taxonomic classification. Moreover, using a SparCC (Sparse Correlations for Compositional data) network construction model, we investigated potential interactions between members of the microbial communities from laboratory-maintained and field-collected ticks. Results Overall, Francisellaceae was the most dominant bacteria identified in the microbiome of both laboratory-raised and field-collected Am. americanum across all tissues and developmental stages. Likewise, microbial diversity was seen to be significantly higher in field-collected ticks compared with laboratory-maintained ticks as seen with a higher number of both Operational Taxonomic Units and measures of species richness. Several potential positive and negative correlations were identified from our network analysis. We observed a strong positive correlation between Francisellaceae, Rickettsiaceae, and Midichloriaceae in both developmental stages and tissues from laboratory-maintained ticks, whereas ovarian tissues had a strong positive correlation of bacteria in the family Xanthobacteraceae and Rhizobiaceae. A negative interaction was observed between Coxiellaceae and Francisellaceae in Illinois, and all the bacteria detected from ticks from Delaware were negatively correlated. Conclusion This study is the first to catalog the microbiome of Am. americanum throughout its developmental stages and different tissue niches and report the potential replacement of Coxiellaceae by Francisellaceae across developmental stages and tissues tested except in ovarian tissues. These unique and significant findings advance our knowledge and open a new avenue of research to further understand the role of tick microbiome in tick-borne diseases and develop a holistic strategy to control alpha-gal syndrome.